Strategies Used By Students’ In Writing English Text - Sitti Fitriawati Mamudi; Ella Fadila (Sintuwu Maroso Journal of English Teaching, 2022)
The objective of the research is to find out the writing strategies used by thestudents in English language EducationStudy Program of Sintuwu Maroso. The type of this research is quantitative research using survey method. The instrument of data collection was questionnaire and interview. The data is analyzed bydetermining from the average of scores students choose in each item of statements which is ranging from 1-5, which are: (1).Highly used (Mean score=M) between 3.5 to 5.0 indicates that all four of strategies are the most frequently used by the participants. (2).Medium used (M) between 2.5 to 3.4indicates that all four of strategies are normally used by the participants.(3).Low used (M) smaller than 2.4 indicates all four of strategies are rarely used by the participant. The finding of research obtained that the strategies in writing highly used by students of English Language Study Program in Sintuwu Maroso University are Metacognitive strategy, Cognitive strategy, Affective strategy and Social strategy/ all of strategy is frequesntly used by the students in writing English Text.